A Philosophical Juridical Study on the Best Interests of Children in the Juvenile Criminal Justice System - Supriyanta (Universitas Muhammadiyah Palu, 2024)
Children's rights must be upheld and implemented in all nations that have established conventions on children's rights. This includes taking all necessary legislative and other steps. This is because only children can determine whether a decision or policy will be applied to them, whether it is good or bad, it must be prioritized for the best interests of the child, one of which is by implementing the resolution of cases of children in conflict with the law, a child should not be punished, but they should given protection and assistance. The aim of this research is to find out how the principle of the best interests of children is regulated in the SPPA Law. The method used is normative juridical. The research found that cases involving children must be resolved according to the juvenile criminal justice system through diversion which must be pursued at every stage of the criminal justice system. This is important for the child's future fulfillment and opportunity to become a productive and responsible individual. Children need to be protected through the principle of the child's best interests. According to the principle of the best interests of the child, all decisions regarding children, including those made by parents, society and the government, must be made by considering the best interests of the child.